A Phase 3, Randomized, Placebo‐Controlled Evaluation of the Safety of Intravenous Meloxicam Following Major Surgery. Issue 8 (20th February 2019) - Bergese, Sergio D.; Melson, Timothy I.; Candiotti, Keith A.; Ayad, Sabry S.; Mack, Randall J.; McCallum, Stewart W.; Du, Wei; Gomez, Alexis; Marcet, Jorge E.
Abstract: An intravenous (IV) formulation of meloxicam is being studied for moderate to severe pain management. This phase 3, randomized, multicenter, double‐blind, placebo‐controlled trial evaluated the safety of once‐daily meloxicam IV 30 mg in subjects following major elective surgery. Eligible subjects were randomized (3:1) to receive meloxicam IV 30 mg or placebo administered once daily. Safety was evaluated via adverse events, clinical laboratory tests, vital signs, wound healing, and opioid consumption. The incidence of adverse events was similar between meloxicam IV– and placebo‐treated subjects (63.0% versus 65.0%). Investigators assessed most adverse events as mild or moderate in intensity and unrelated to treatment. Adverse events of interest (injection‐site reactions, bleeding, cardiovascular, hepatic, renal, thrombotic, and wound‐healing events) were similar between groups. Over the treatment period, meloxicam IV was associated with a 23.6% ( P = .0531) reduction in total opioid use (9.2 mg morphine equivalent) compared to placebo‐treated subjects. The results suggest that meloxicam IV had a safety profile similar to that of placebo with respect to numbers and frequencies of adverse events and reduced opioid consumption in subjects with moderate to severe postoperative pain following major elective surgery.